Extending SIT to Niche Networks: The Effect of Group Commitment on Sexual Identity Commitment among Men who have Sex with Men - Coker, Michael; Kahlow, Jessica (Human Communication & Technology, 2021)
Niche networks for sexual minorities are becoming increasingly popular and have garnered significant scholarly attention. Adding to the ongoing conversation regarding the uses and effects of niche networks, we explore the motivations for and impact of engaging with GPS-based hookup applications on sexual identity and group commitment. Using a cross-sectional survey of a nationwide sample (N = 102) and social identity theory (Tajfel, 1978), we investigate the effect of group commitment and motivations on daily hookup application use and sexual identity commitment among men seeking men. Findings demonstrate that group commitment and sexual identity commitment are positively correlated among GPS-based hookup application users, and that group commitment moderates the relationship between daily application use and sexual identity commitment. Further, the association between group commitment and sexual identity commitment is moderated by users’ motivations. Specifically, long-term motivations for using GPS-based hookup applications strengthens the association between group commitment and sexual identity commitment among app users. A significant association existed between group commitment and sexual identity commitment for participants whose primary motivation was long-term, but no association existed for participants whose primary motivation was short-term. This study extends niche network research and social identity theory by situating hookup applications as a social context for experiencing cognitive connections with group members and exploring sexual identity.